The Effect of Service Quality on Customer Satisfaction at Securities Companies - Muhmin, Andi Hidayat (Majalah Ilmiah Bijak, 2023)
This research aims to investigate the influence of service quality on customer satisfaction in the context of securities companies using the SERVQUAL approach. Securities companies have a crucial role in the financial markets, and customer satisfaction is a vital indicator in maintaining and increasing their market share. The SERVQUAL approach is used as a framework for measuring service quality by identifying five main dimensions: tangibles, reliability, responsiveness, assurance, and empathy.The research methodology involves surveying customers of randomly selected securities firms. The data collected is then analyzed using relevant statistical methods to test the relationship between service quality variables and customer satisfaction. In addition, this study also considers demographic factors and customer experience as possible control variables influencing results.It is hoped that the results of this research will provide a better understanding of how aspects of service quality, such as speed in responding to customer questions, the accuracy of information provided, and the level of empathy of securities company staff, influence the level of customer satisfaction. These results are expected to help securities firms improve their service strategies, increase customer retention, and gain a competitive advantage in an increasingly competitive marketplace.This research is expected to provide valuable information for company executive securities, financial industry practitioners, and other researchers who are interested in understanding the dynamics of the relationship between service quality and customer satisfaction in the context of securities companies. Apart from that, this research can also be a basis for further research that explores other factors that influence customer satisfaction and effective strategies to increase it